2020
DOI: 10.26508/lsa.201900586
|View full text |Cite
|
Sign up to set email alerts
|

Keratinocyte interleukin-36 receptor expression orchestrates psoriasiform inflammation in mice

Abstract: The IL-36 family cytokines have emerged as important mediators of dermal inflammation in psoriasis and have been reported to provide a proinflammatory stimulus to a variety of immune and stromal cell subsets in the inflamed skin. However, it remains to be determined which cell type, if any, in the skin plays a predominant role in mediating IL-36 cytokines instructive role in disease. Here, we demonstrate that targeted deletion of Il36r in keratinocytes results in similar levels of protection from psoriasiform … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 38 publications
2
25
2
Order By: Relevance
“…However, we observed that K14Cre mice, but not K5Cre mice, were partly resistant to Aldara-induced psoriasis-like dermatitis. This difference may explain the difference between our data and those observed by Hernandez-Santana et al (2020).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…However, we observed that K14Cre mice, but not K5Cre mice, were partly resistant to Aldara-induced psoriasis-like dermatitis. This difference may explain the difference between our data and those observed by Hernandez-Santana et al (2020).…”
Section: Discussioncontrasting
confidence: 99%
“…While we were submitting this manuscript, another study performed with comparable methodology than ours demonstrated a similar resistance to Aldara-induced psoriasis-like dermatitis in K14Cre × Il36r fl/fl (DK14) mice than in Il36r-deficient mice, which corroborates our results (Hernandez-Santana et al, 2020). However, they observed some differences compared with our study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…IL-36Ra expression was increased in psoriatic skin in mouse models or patients ( 79 , 116 118 , 178 , 180 , 195 , 199 204 ). IL-36 signaling in keratinocytes is mandatory for the development of Aldara (5% IMQ)-induced psoriasis ( 79 , 205 ), suggesting that the observed increase in IL-36Ra is insufficient to counterbalance the effects of agonistic IL-36 cytokines. Indeed, Il1f5 is strongly induced in skin of Aldara (5% IMQ)-treated mice ( 79 , 195 ), and IL-36α- but not IL-36β- or IL-36γ-deficient mice are protected in this model ( 206 ).…”
Section: Natural Antagonists and Anti-inflammatory Il-1 Family Cytokimentioning
confidence: 99%
“…Indeed, Il1f5 is strongly induced in skin of Aldara (5% IMQ)-treated mice ( 79 , 195 ), and IL-36α- but not IL-36β- or IL-36γ-deficient mice are protected in this model ( 206 ). Another hypothesis could be related to the important, IL-36-mediated, neutrophil infiltration in psoriatic skin ( 24 , 79 , 205 ). Indeed, the supernatant of PMA-treated neutrophils has been shown to induce cleavage of IL-36Ra into the inactive S4 form ( 196 ).…”
Section: Natural Antagonists and Anti-inflammatory Il-1 Family Cytokimentioning
confidence: 99%